Analysis of Employee Welfare, Work Environment and Social Support on Employee Performance Through Organizational Commitment inPT PLN (Persero) Regulatory Implementing Unit Distribution (UP2D) North Sumatera - Muhammad Yunan; Erwansyah (Equivalent : Journal of Economic, Accounting and Management, 2026)
This study aims to investigate the impact of employee well-being, work environment, and social support on employee performance, considering organizational commitment as a mediating variable at PT PLN (Persero) Distribution Regulation Implementation Unit (UP2D) North Sumatra. A quantitative research design was employed, employing survey methodology. Data were collected through questionnaires distributed to 117 employees. Data analysis was conducted using Structural Equation Modeling (SEM) using Partial Least Squares (PLS) techniques. The findings indicate that employee well-being and the work environment significantly and positively influence employee performance. Furthermore, employee well-being and social support contribute positively and significantly to organizational commitment. Organizational commitment itself also positively impacts employee performance. However, social support did not have a significant direct effect on employee performance, and the work environment did not significantly influence organizational commitment. Furthermore, the results of the indirect effect test indicate that employee well-being and social support significantly influence employee performance through organizational commitment. Conversely, the work environment did not significantly influence employee performance through organizational commitment. These results underscore the importance of organizational commitment as a key mediating variable in strategies aimed at improving employee performance, particularly through strengthening employee well-being and social support.